2019
DOI: 10.1186/s12864-018-5395-1
|View full text |Cite
|
Sign up to set email alerts
|

Banana sRNAome and degradome identify microRNAs functioning in differential responses to temperature stress

Abstract: BackgroundTemperature stress is a major environmental factor affecting not only plant growth and development, but also fruit postharvest life and quality. MicroRNAs (miRNAs) are a class of non-coding small RNAs that play important roles in various biological processes. Harvested banana fruit can exhibit distinct symptoms in response to different temperature stresses, but the underlying miRNA-mediated regulatory mechanisms remained unknown.ResultsHere, we profiled temperature-responsive miRNAs in banana, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 57 publications
0
55
1
Order By: Relevance
“…It became apparent that to identify changes in the plant sRNA response to virus (or any other biotic or abiotic stress), a global meta-network of interactions between sRNAs and transcribed RNA targets was required that could serve as reference for mapping changes. Changes in crop plant sRNA responses are being studied to improve crop productivity and better understand responses to drought (Zheng et al, 2019), nutritional stress (dos Santos et al, 2019), cold (Ghildiyal and Zamore, 2009;Bustamante et al, 2018;Zhu et al, 2019), and metal toxicity (Wang et al, 2019). Plant sRNAs regulate innate immunity to pathogens (Deng et al, 2018) and cross-kingdom RNA trafficking is being exploited as a crop protection strategy (Cai et al, 2018); the mechanism underlying these latter processes is sRNA-mediated RNA interference.…”
Section: Introductionmentioning
confidence: 99%
“…It became apparent that to identify changes in the plant sRNA response to virus (or any other biotic or abiotic stress), a global meta-network of interactions between sRNAs and transcribed RNA targets was required that could serve as reference for mapping changes. Changes in crop plant sRNA responses are being studied to improve crop productivity and better understand responses to drought (Zheng et al, 2019), nutritional stress (dos Santos et al, 2019), cold (Ghildiyal and Zamore, 2009;Bustamante et al, 2018;Zhu et al, 2019), and metal toxicity (Wang et al, 2019). Plant sRNAs regulate innate immunity to pathogens (Deng et al, 2018) and cross-kingdom RNA trafficking is being exploited as a crop protection strategy (Cai et al, 2018); the mechanism underlying these latter processes is sRNA-mediated RNA interference.…”
Section: Introductionmentioning
confidence: 99%
“…One SNP in the MAPK14 (rs851023) was significantly associated with incident PCa risk. Compared to men carrying two copies of allele A, the presence of one or two copies of the G allele was associated with decreased risk of PCa, (Zhang et al, 2019).…”
Section: Rna and Evolutionmentioning
confidence: 93%
“…Gilbert (1978) proposed that exons and domains could be recombined to produce new chimeric genes. In addition, retroposed sequences may jump into or near existing genes and recruit existing exons, or to be recruited into an existing coding sequence, (Zhang et al, 2009). Xue et al, (2003) found that the Epstein-Barr virus contains an early gene that undergoes frequent frameshifts, probably to combat host immunity.…”
Section: Image©edvotek 2014mentioning
confidence: 99%
See 1 more Smart Citation
“…The 67 target genes fell into three categories (0, 1, and 3). Approximately 85% (57 genes) of them were in category 0, which represents the most abundant degradome tags corresponding to the cleavage site and matching cognate transcripts (Zhu et al, 2019). The highest number of targets (60) was identified for IS, and the lowest number was identified for NIS (35).…”
Section: Identification Of Mirna Target Genes By In Silico and Degradmentioning
confidence: 99%